Electronic communication of cells with a surface mediated by boronic acid saccharide interactions - Stephenson-Brown, Alex; Yong, Sue; Mansor, Muhammad H.; Hussein, Zarrar; Yip, Nga-Chi; Mendes, Paula M.; Fossey, John S.; Rawson, Frankie J. (Royal Society of Chemistry, 2015)
The fabrication of a molecularly tailored surface functionalised with a saccharide binding motif, a phenyl boronic acid derivative is reported.The functionalised surface facilitated the transfer of electrons, via unique electronic interactions mediated by the presence of the boronic acid, from a macrophage cell line. This is the first example of eukaryotic cellular-electrical communication mediated by the binding of cells via their cell–surface saccharide units.